The Existence of Multicultural Education in Facing Radicalism - Siti Ngaisah; Yasin Nurfalah (eL Bidayah: Journal of Islamic Elementary Education, 2020)
This research, was born from a small part of anxiety over the understanding of radicalism in educational institutions. Many researchers claim that the spread of radicalism in Indonesia has been very acute, the article has spread to elementary students. Nevertheless, many are optimistic that multiculturalism education is one of the antidotes to the understanding of radicalism. This encourages researchers to assess the existence of multiculturalist education in facing radicalism in the Wanengpaten State Elementary School, Gampengrejo District, Kediri. This study uses a descriptive qualitative approach. The method used is, interviews with stakeholders at the institution, observing activities in implementing multicultural education values and tracking documents related to the educational institution. As a result, the key to counteract radicalism is religious understanding and awareness of the dangers of radicalism. Without it, the de-radicalization program would not be possible. [Penelitian ini, lahir dari bagian kecil kegelisahan mengatasi paham radikalisme di lembaga-lembaga pendidikan. Banyak peneliti menyatakan bahwa penyebaran radikalisme di Indonesia sudah sangat akut, pasalnya sudah menyebar pada peserta didik dasar. Meski demikian, banyak pula yang optimis bahwa pendidikan multikulturalisme menjadi salah satu penangkal paham radikalisme. Hal ini, mendorong peneliti untuk mengakasi eksistensi pendidikan multikulturalis dalam menghadapi paham radikalisme di Sekolah Dasar Negeri (SDN) Wanengpaten, Kecamatan Gempengrejo, Kabupaten Kediri, Penelitian ini menggunakan pendekatan kualitatif diskriptif. Metode yang digunakan adalah, waancara kepada stakeholder pada lembaga tersebut, observasi kegiatan dalam implemantasi nilai-nilai pendidiakn multikulturalisme dan melacak dokumen-dokumen terakait lembaga pendidikan tersebut. Hasilnya, kunci menangkal radikalisme adalah pemahaman keagamaan dan sadar bahaya radikalisme. Tanpa itu, program deradikalisasi tidak mungkin bisa dilaksanakan.]